Seven Pillars of Survivability: Appropriate Technology with a Human Face - Sianipar, Corinthias Pamatang Morgana; Dowaki, Kiyoshi; Yudoko, Gatot; Adhiutama, Akbar (European Journal of Sustainable Development, 2013)
There were evidence for the inappropriateness of just three pillars of sustainability whenengineers have attempted to construct appropriate technology for underdevelopedcommunities. Engineers from developed countries have tended to conduct technologicaladaptations by treating communities as objects, rather than engaging them as subjects ofdevelopment. As objects, communities could not decide what they wanted to be and wereeven forced into systematic development that was more likely to benefit the developedcountries. However, as subjects, communities can determine their own sustainability andachieve survivability. In this study, seven pillars of survivability are outlined: technical,economic, environmental, social, cultural, judicial, and political. The first three aretangible aspects, and the last three are intangible. The social aspect is the intermediary, thebridge to emerging technological appropriateness. Tangible aspects can be measurednumerically, whereas the intangible ones cannot. The tangible and intermediate aspectsare what engineers must address, and both the intermediate and the intangible ones arewhat they must address specifically to diffuse appropriate technology into local dailyroutines. Tiers of technological appropriateness are also provided to understand theposition of a designed appropriate technology in terms of survivability levels. A holisticapproach that takes these pillars into account will empower communities to reach self-survivability beyond sustainability.